x+5(x-5)=11

Simple and best practice solution for x+5(x-5)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+5(x-5)=11 equation:


Simplifying
x + 5(x + -5) = 11

Reorder the terms:
x + 5(-5 + x) = 11
x + (-5 * 5 + x * 5) = 11
x + (-25 + 5x) = 11

Reorder the terms:
-25 + x + 5x = 11

Combine like terms: x + 5x = 6x
-25 + 6x = 11

Solving
-25 + 6x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + 6x = 11 + 25

Combine like terms: -25 + 25 = 0
0 + 6x = 11 + 25
6x = 11 + 25

Combine like terms: 11 + 25 = 36
6x = 36

Divide each side by '6'.
x = 6

Simplifying
x = 6

See similar equations:

| 3g+2g+5=0 | | Q^2+16q-15=0 | | 2(3+q)+q=3 | | 4-10-4-(-3)+3= | | an=1+(-1)n | | =2b*a | | 6(r+0.5)=r | | =2axb | | 5z+3=8z-4z | | h=-16t^2+132t+5 | | 0=32t^2+12t | | 3(r+0.5)=r | | 5(x+4)+2x=3(5x-4)-10x | | y^8+8y^4+16=0 | | 1=7.5x | | 7w-4/3=-4/3w-3/4 | | 2n-5=7c | | 6+2(3x-1)=-8 | | 4xy+1=0 | | 6+2(3x-1)=8 | | 2-bracket(-5)= | | -3/10h=5 | | 18=(x*36)+(y*18) | | 7a-5+a-3-8a= | | 14v^8w^7x^5-28v^2w^8=0 | | 25j=5 | | 2r-9s=-73 | | 3(z+4)=9 | | 48-w=158 | | 3.14+3x=10 | | 5a-6-6a+4+a= | | 3p-4m-7= |

Equations solver categories